2000
DOI: 10.1139/t99-107
|View full text |Cite
|
Sign up to set email alerts
|

Mass loading and the rate of clogging due to municipal solid waste leachate

Abstract: The results of laboratory column tests conducted to assess the effect of the mass loading on the clogging of porous media are presented. The tests were conducted using actual leachate from the Keele Valley Landfill under saturated, anaerobic conditions. It is shown that clogging is greatest where there is the greatest mass loading (near the inlet in this case, but likely near the collection pipes in a field situation). An empirical relationship between the hydraulic conductivity and drainable porosity is prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 9 publications
(13 reference statements)
1
12
0
Order By: Relevance
“…This hindered the supply of nutrients and calcium to the other sections of the columns where lower clog formation rates were measured. A similar trend in leachate treatment with column length and the resulting distribution of hard inorganic clog material was observed by Rowe et al (2000a). However, in the gravel column, although smaller amounts of COD and calcium were removed as the leachate traveled through the column, the rate of clog formation and the drainable porosity measurements (discussed later) for each section indicate that there was a relatively uniform development of clog in each section, which suggests that some mechanism other than direct precipitation of calcium to form hard inorganic clog material on the fixed drainage medium was affecting clog development in this column.…”
Section: Leachate Quality Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…This hindered the supply of nutrients and calcium to the other sections of the columns where lower clog formation rates were measured. A similar trend in leachate treatment with column length and the resulting distribution of hard inorganic clog material was observed by Rowe et al (2000a). However, in the gravel column, although smaller amounts of COD and calcium were removed as the leachate traveled through the column, the rate of clog formation and the drainable porosity measurements (discussed later) for each section indicate that there was a relatively uniform development of clog in each section, which suggests that some mechanism other than direct precipitation of calcium to form hard inorganic clog material on the fixed drainage medium was affecting clog development in this column.…”
Section: Leachate Quality Resultssupporting
confidence: 76%
“…9. Rowe et al (2000a) have suggested an empirical relationship between the hy-draulic conductivity (k, measured in m/s) and the drainable porosity (n) as follows:…”
Section: Hydraulic Conductivity -Drainable Porosity Relationshipmentioning
confidence: 99%
“…12). The degree to which clogging occurrs has been demonstrated to be greatest under higher mass loading rates to the LCRS (Fleming et al 1999;Rowe et al 2000). While landfills subjected to liquids addition result in greater leachate flow, the concentrations of biodegradable organic matter (BOD) are expected to become lower than conventional landfills more rapidly.…”
Section: Clogging Potential In Sustainable Landfill Operationsmentioning
confidence: 99%
“…Brune et al, 1991;Koerner et al, 1994;Fleming et al, 1999Rowe et al, 2000 who have demonstrated the more extensive clogging effects of acidogenic leachates. This is because the clogging potential of methanogenic leachate is so much less than that of acidogenic leachate.…”
Section: Discussionmentioning
confidence: 99%